2021
DOI: 10.1002/ange.202015659
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Nanophosphor Embedded in Mesoporous Silica Nanoparticle with High Light‐Harvesting Efficiency for Dual Photosystem Enhancement

Abstract: Light‐harvesting and conversion ability is important to promote plant growth, and especially when resources are limited. A near‐infrared (NIR) nanophosphor embedded with mesoporous silica nanoparticles (MSN), ZnGa2O4:Cr3+,Sn4+ (ZGOCS), was developed and its optical properties were harnessed to enhance the photosynthetic ability of Brassica rapa spp. chinensis. The broad excitation of ZGOCS from the ultraviolet to the visible region allowed the conversion of extra light into near‐infrared light (650–800 nm) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…32 Since then, multiple studies have also synthesized the nanocomposite with other dopants (Sn 4+ , and Yb 3+ ) to enhance the optical properties. [33][34][35] In these studies, CZGO were confined within the MSN template, and the overall particle sizes were between 50 nm to 100 nm. Microscopy images have also revealed the sizes of the CZGO nanoparticles were all below 10 nm, which is smaller than any other synthesis approaches reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…32 Since then, multiple studies have also synthesized the nanocomposite with other dopants (Sn 4+ , and Yb 3+ ) to enhance the optical properties. [33][34][35] In these studies, CZGO were confined within the MSN template, and the overall particle sizes were between 50 nm to 100 nm. Microscopy images have also revealed the sizes of the CZGO nanoparticles were all below 10 nm, which is smaller than any other synthesis approaches reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In the past years, chromium-activated ZnGa 2 O 4 is being considered as one of the most fascinating optical materials due to its outstanding and bright near-infrared photoluminescence, efficient persistent luminescence, long afterglow, high light harvesting efficiency, wavelength tunability, and superior photostability. 2,3,[9][10][11][12][13] Consequently, ZnGa 2 O 4 :Cr 3+ (ZGOC) has found wide range applications in areas such as bioimaging, optical sensors, optical information storage, drug delivery, and plant growth. 2,9,10,13,14 However, there is still continuous ongoing effort in the global research community to explore more functionalities, add new dimensions, and improve the optical properties of ZGOC nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,[9][10][11][12][13] Consequently, ZnGa 2 O 4 :Cr 3+ (ZGOC) has found wide range applications in areas such as bioimaging, optical sensors, optical information storage, drug delivery, and plant growth. 2,9,10,13,14 However, there is still continuous ongoing effort in the global research community to explore more functionalities, add new dimensions, and improve the optical properties of ZGOC nanoparticles. The most critical issues with nanocrystals are their associated higher surface area, which quench the luminescence by providing additional channels for non-radiative relaxation and adversely curtail the inventions and application of new functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent rare earth ions are selected in a suitable combination to meet the uorescence requirements from the UV band all the way to the IR band, which have abundant energy levels. 17,18 Zhu et al reported Cr 3+ -doped AlP 3 O 9 displaying broadband NIR emission from 650-1000 nm with $76% luminescence internal quantum efficiency (IQE). 19 KGaP 2 O 7 exhibits a broadband NIR emission peak at 815 nm when Cr 3+ is added in a weak crystal eld environment.…”
Section: Introductionmentioning
confidence: 99%